Informační systém pro prodejce kosmetiky Oriflame - Kyncl, Matěj (Vysoké učení technické v Brně. Fakulta informačních technologií)
Cílem této bakalářské práce je vytvořit informační systém pro prodejce kosmetiky Oriflame. Popisuje základní funkce a vlastnosti databází, dále jsou zachyceny běžně používané technologie pro tvorbu dynamických webových stránek - PHP, Javascript. Další kapitoly se zabývají analýzou a návrhem informačního systému. Závěrečná část práce popisuje samotnou implementaci navrženého systému.

The goal of this bachelor's thesis is to create the information system for Oriflame cosmetics sellers. It describes basic functions and properties of the databases, further the commonly used technologies for dynamic web pages creation are presented - PHP, Javascript. The following chapters deal with the analysis and proposition of the information system. The final part of the work describes the implementation of the designed system itself.
Information System for Oriflame Cosmetics Sellers
Keywords: Informační systém; MySQL; SQL; relační databáze; PHP; HTML; Javascript; CSS; Information system; MySQL; SQL; relation database; PHP; HTML; Javascript; CSS